Comparison between Combination of Proximal Adductor Canal Block and Infiltration between Popliteal Artery and Capsule of Knee (iPACK) with Large-Volume Distal Adductor Canal Block in Facilitating Early Mobilization after Total Knee Replacement: A Randomized, Single-Blind Study - Pryambodho Pryambodho; Lawrence Kwan; Aida Rosita Tantri; Andri Maruli Tua Lubis (Bali Journal of Anesthesiology, 2024)
Background: Adductor canal block (ACB) and infiltration between popliteal artery and capsule of knee (iPACK) are popular block methods for analgesia after total knee replacement (TKR), covering both the anterior and posterior knee. This study aimed to compare the performance of the combination of ACB and iPACK with large-volume distal ACB in facilitating early mobilization after TKR.